Does recombinant human erythropoietin administration in critically ill COVID‐19 patients have miraculous therapeutic effects?. Issue 7 (19th April 2020) - Hadadi, Azar; Mortezazadeh, Masoud; Kolahdouzan, Kasra; Alavian, Golbarg
Abstract: An 80‐year‐old man with multiple comorbidities presented to the emergency department with tachypnea, tachycardia, fever, and critically low O2 saturation and definitive chest computerized tomography scan findings in favor of COVID‐19 and positive PCR results in 48 hours. He received antiviral treatment plus recombinant human erythropoietin (rhEPO) due to his severe anemia. After 7 days of treatment, he was discharged with miraculous improvement in his symptoms and hemoglobin level. We concluded that rhEPO could attenuate respiratory distress syndrome and confront the severe acute respiratory syndrome coronavirus 2 virus through multiple mechanisms including cytokine modulation, antiapoptotic effects, leukocyte release from bone marrow, and iron redistribution away from the intracellular virus. Highlights: – Recombinant human erythropoietin can rapidly correct anemia and symptoms associated with COVID‐19 – Through cytokine modulation, rhEPO exerts its cytoprotective and anti‐apoptotic effects in COVID pneumonia. – rhEPO takes iron away from intracellular virus into the bone marrow, undermining the viral enzymatic requirements.